Determination of Tellurium by Radiochemical Displacement - Aruna, K.; Naidu, N.V.S. (Asian Journal of Chemistry, 2011)
A rapid and sensitive method for the determination of tellurium(IV) by the displacement of radio cobalt from its diethyl dithiocarbamate complex in CCl4 is reported. pH 5 in acetate buffer was found suitable for the quantitative displacement. Effect of diverse metal ions on the displacement were studied. Most of the ions generally associated with tellurium does not interfere and the interference due to Fe(III) and Sb(III) was masked with oxalate. Interference due to other ions was overcome by prior collection of tellurium on Al(OH)3. Calibration was linear and accurate in the range 2-16 μg Te. Samples of cadmium oxide, copper metal, stream sediments and Sb-In alloy were analyzed.